Moving from Vaccine Hesitancy to Acceptance: Engaging Underrepresented Employees in a Pediatric Academic Medical Center. Issue 2 (10th March 2023) - Connor, Jean A.; Fynn-Thompson, Francis; Horgan, James J.; Luff, Donna; Hickey, Patricia A.; Ward, Valerie L.
Abstract : Introduction: Underrepresented populations historically underserved by the healthcare system and/or marginalized by systematic policies regionally and nationally were particularly vulnerable during the COVID-19 pandemic. While vaccine hesitancy has been described among hospital employees, the employees' experiences from an underrepresented population cohort have not been reported. We, therefore, sought to understand employees' vaccine experiences, hesitancy, and ways to enhance ongoing COVID-19 vaccine education and communication to build a hospital-wide culture of vaccine acceptance. Methods: We invited interprofessional staff from 5 clinical departments to participate in qualitative focus groups. Guiding questions were used to explore the experiences and perceptions of the staff. Using content analysis, we identified themes and recommendations for improvement. Results: We conducted 5 focus group sessions with over 50 participants. Four themes emerged; "Vaccine Fears Past and Present, " "Access to Information, " "Worries for Families, " and "Our Hospital is a Trusted Name." Participants also provided recommendations for improvement in the messaging around the vaccine rollout. Consideration of how different employees access information, listening to staff needs, and recognizing the role of race and history were critical to engaging and improving the underrepresented employees' vaccine acceptance. Conclusions: Exploring the concerns and fears of the COVID-19 vaccine within groups of underrepresented staff members through qualitative methods was key to understanding their vaccine hesitancy and implementing strategies to move toward vaccine acceptance in the hospital.